Management of closed shaft of humerus fractures in non admitted adult patients in a tertiary care hospital - Arfee, Sakib; Rashid, Mudasir; Bhat, Imran Yousouf; Verma, Sandeep; Tahir, Syed Rouf (International Journal of Research in Orthopaedics, 2019)
Background: Fracture shaft humerus is among the most common of fractures. Proximal fractures are more common in elderly and are commonly attributed to low-energy falls, they make up to 5% of all fractures and 25% of humerus fractures, middle fractures about 60% and distal fractures contribute to the remaining fractures. Fractures shaft of humerus account for approximately 3% of all fractures encountered by the orthopedic surgeons. Methods: From November 2017 to October 2018 sixty-two fractures of humeral shaft presented at Emergency Orthopedic Department in Government Medical College Jammu, 30 fractures considered suitable for the study. All these patients were treated conservatively by using the Coaptation ‘U’ shaped slab discharged the next day and evaluation done both clinically and radiologically every two weeks. Results: This study showed that the angulation deformities were considerably reduced by the use of U slab and the POP cast. Smoking appeared to have negative effect on the rate of union. Conclusions: Conservative treatment is one of the most effective methods of treatment. Operative treatment should be limited as much as possible to specific indications given below.